Susceptibilities of MDR Mycobacterium tuberculosis isolates to unconventional drugs compared with their reported pharmacokinetic/pharmacodynamic parameters. (20th February 2017) - Cavanaugh, Joseph S.; Jou, Ruwen; Wu, Mei-Hua; Dalton, Tracy; Kurbatova, Ekaterina; Ershova, Julia; Cegielski, J. Peter; ,
Abstract : Background: The second-line drugs recommended to treat drug-resistant TB are toxic, expensive and difficult to procure. Given increasing resistance, the need for additional anti-TB drugs has become more urgent. But new drugs take time to develop and are expensive. Some commercially available drugs have reported anti-mycobacterial activity but are not routinely used because supporting laboratory and clinical evidence is sparse. Methods: We analysed 217 MDR M. tuberculosis isolates including 153 initial isolates from unique patients and 64 isolates from follow-up specimens during the course of treatment. The resazurin microdilution assay was performed to determine MICs of trimethoprim/sulfamethoxazole, mefloquine, thioridazine, clofazimine, amoxicillin/clavulanate, meropenem/clavulanate, nitazoxanide, linezolid and oxyphenbutazone. Isoniazid was used for validation. We calculated the MIC50 and MIC90 as the MICs at which growth of 50% and 90% of isolates was inhibited, respectively. Results: The MIC50 s, in mg/L, for initial isolates were as follows: trimethoprim/sulfamethoxazole, 0.2/4; mefloquine, 8; thioridazine, 4; clofazimine, 0.25; amoxicillin/clavulanate, 16/8; meropenem/clavulanate, 1/2.5; nitazoxanide, 16; linezolid, 0.25; and oxyphenbutazone, 40. The MIC90 s, in mg/L, for initial isolates were as follows: trimethoprim/sulfamethoxazole, 0.4/8; mefloquine, 8; thioridazine, 8; clofazimine, 0.5; amoxicillin/clavulanate, 32/16; meropenem/clavulanate, 8/2.5; nitazoxanide, 16; linezolid, 0.25; and oxyphenbutazone, 60. By comparison, the MIC90 of isoniazid was >4 mg/L, as expected. There was no evidence that previous treatment affected susceptibility to any drug. Conclusions: Most drugs demonstrated efficacy against M. tuberculosis . When these MICs are compared with the published pharmacokinetic/pharmacodynamic profiles of the respective drugs in humans, trimethoprim/sulfamethoxazole, meropenem/clavulanate, linezolid, clofazimine and nitazoxanide appear promising and warrant further clinical investigation.